Implementing patient safety : addressing culture, conditions, and values to help people work safely - Suzette Woodward (Abingdon, Oxon : Routledge/Productivity Press, 2020)
Over the last two decades across the globe we have seen a multitude of programs, projects and books to help improve the safety of patient care in healthcare. However, the full potential of these has not yet been reached. Most of the current approaches are top down, programmatic and target driven. These look at problems in isolation one harm at a time with simplistic solutions that fail to support a holistic, systematic approach. They are focused on collecting incident data and learning from failure using tools that are not fit for purpose in a complex nonlinear system. Very rarely do the solutions help build the conditions, cultures and behaviours that support a safer system and help the people involved work safely. Healthcare is stuck in a relentlessly negative approach to safety. Those working in patient safety and healthcare are struggling, and books on patient safety to date instruct the reader to continue doing the same things we have been doing for the last 20 years. This book uniquely combines the latest thinking in safety, including creating a balanced approach to learning from what works as a way to understand why it fails, together with the evidence on building a just culture, positive workplaces and working relationships that we now know are so important for safety. It helps people understand how to address issues despite their complexities and improve safety with practical ways to truly understand what day to day healthcare work is actually like, rather than what people imagine it is like. This book builds on the author's first book Rethinking Patient Safety which exposed what we need to do differently to truly transform our approach to patient safety. It updates the reader further on the concepts explored in the first book but also vitally helps readers understand the how'. Implementing Patient Safety goes beyond the rhetoric and provides the reader with ideas and examples for how the latest thinking can actually be achieved. It is based on the author's personal experience of leading a national culture change campaign in the National Health Service for five years. The lessons arise from helping hundreds of organisations and people rethink and implement a whole new way of thinking about improving patient safety in healthcare
Keywords: BUSINESS & ECONOMICS Production & Operations Management; MEDICAL Hospital Administration & Care; BUSINESS & ECONOMICS Quality Control